ANALISA AKAD AS-SHARF DALAM TUKAR MENUKAR (DINAR DIRHAM) DALAM PEMIKIRAN SYAIKH TAQIYUDDIN AN-NABHANI - Mohammad Ghozali; Muhamad Annas (Jurnal Ekonomi Syariah Darussalam, 2024)
The purpose of this study is to find out the as-sharf contract in exchanging currency according to Islamic law, to find out the as-sharf contract according to Sheikh Taqiyuddin an-Nabhani and to find out how the reality occurs in the exchange of as-sharf contracts. This study is a qualitative study by reviewing various literatures that are relevant to the subject matter, and Gerai Dinar as the object of research to find out the real reality, using the literature review method, observation and by interview and further documentation using data analysis techniques using the deductive method. The results of the study indicate that as-sharf transactions are permitted on condition that they must be in cash or directly and must not be more than what is exchanged. If there is an excess, then that is called usury and the law is haram. On the other hand, the function of money is only as a means of exchange and a means of calculating units of goods. If someone makes a sale and purchase of currency, then the law is haram, because money cannot be used as a commodity.